Professional stressors in prison officers: a cross-sectional study - Paleksić, Vesna M (Scripta Medica, 2020)
Background/Aim: The aim of this study was to analyse the stressors on prison officers’ workplace in facilities of closed and semi-open type and their differences and the interconnection between specific sociodemographic variables (sex, age, marital status, exposed working experience, education level) and stressors on workplaces. Methods: The cross-sectional study included 330 prison officers, between 19 and 65 years of age, who have been divided in two groups depending on the security level of the facility (semi-open and close facility type). The research was conducted during 2015, using the following questionnaires: sociodemographic questionnaire, the organisational police stress questionnaire (PSQ.org) and the operational police stress questionnaire (PSQ.op).Results: The results have shown significantly higher load with organisational and operative stress in facilities of closed type (p < 0.001) and that in both groups operative stress sources were slightly more represented than the organisational. The intensity of stress ranged from low to medium. Higher intensity of organisational stress was perceived regarding stressors related to work appreciation, than in regard to sources related to logistic support, while the lowest intensity of stress was in regard to interpersonal relations in the organisation. In closed facilities, divorced prison officers and those who were separated from their families for a longer time have experienced higher stress intensity. Total work experience and age of prison officers had a moderate and mild effect, respecitively, on organisational stressors in higher security facilities. “Fatigue”, “traumatic event” and “favouritism” were the most important stressors. Conclusion: The prison officers are exposed to stress of low to medium intensity, the operational stress sources being more represented then organisational. In higher security facilities total work experience and age had an influence on organisational stressors.
Keywords: Prisons; Stress, psychological; Workplace; Occupational stress; Cross-sectional studies